Apophatic Theology in the Perspective of Deconstructive Hermeneutics - Arifka, Angga (YASIN, 2025)
This article aims to explore apophatic theology in the light of deconstructive hermeneutics, wherein the two are complementary approaches to understanding divine transcendence and the limitations of human language. With a qualitative approach, this article reads apophatic theology employing the hermeneutical theory of Jacques Derrida. This article found that apophatic theology emphasizes the inability of language to fully describe the nature of the Ultimate Reality or God through the approach of negation. At the same time, deconstructive hermeneutics, rooted in Derrida’s philosophy, focuses on the instability and limitations of meaning in language. This study has broad theoretical and practical significance. From a theoretical perspective, this study makes a new contribution to contemporary theological studies by showing how deconstructive hermeneutics can enrich the understanding of the methodology of apophatic theology. In particular, this study highlights how deconstruction helps reveal the creative dimension in the negation of apophatic theology, which is often seen as merely the elimination of meaning.